Credit accumulation and modular scheme in higher education in Rwanda : a case study of lecturers' perceptions of implications for lecturers' work. - Ndagijimana, Jean Claude (My University, 2012)
International literature suggests that curriculum changes that have occurred in higher education globally over the last two decades, more specifically the shift from subject-based curriculum to integrated curriculum have been perceived by many academics as having affected their work with regard to course designing, teaching and assessment. Studies of academics’ response to such changes have argued that the way academics perceived these changes and the meanings they made of them influenced the implementation of these curriculum changes. This case study investigates lecturers’ perceptions of how one curriculum reform, the introduction of the Credit Accumulation and Modular Scheme (CAMS) in higher education in Rwanda, has affected lecturers’ work. One of the aims of the study was to analyse how lecturers understand CAMS and the changes it has introduced in their work. A second aim was to analyse how these perceptions and changes are negotiated in their teaching practices. Sixteen lecturers from Kigali Institute of Education were interviewed. Analyses of lecturers’ accounts of their teaching experiences revealed that lecturers espoused the intended changes that CAMS introduced in their work. However, although they claimed that the changes have affected their teaching and teaching arrangements- course designing, teaching and assessment- in actual practices many of them have not always managed to shift their thinking. CAMS requires lecturers to function in teams. However, although they have been trying to do so many of them have not managed to work out how to make more substantive changes to the way they think about the knowledge to be taught, their actual teaching and assessment practices. They have tried to keep boundaries of their disciplines while CAMS requires them to integrate their teaching.
Keywords: Curriculum reform; Integrated curriculum; Outcomes-based curriculum; Modular-based; Teaching teams; Higher education